"To be dead is an unthinkable anomaly" Reversed Necropolitics and the Death Imaginary - Christodoulou, Marina (My University, 2017)
The concept or the theory of Death in the thought of Jean Baudrillard is not given the particular attention it needs. When one speaks of the thought of Baudrillard, one rarely will mention ‘death’ as one of the keywords of his corpus. I think, though, that it deserves such a key place, for three reasons. Firstly, because the theme of Death is a gargantuan concept in the history of Philosophy and it even emerges with the definition of Philosophy itself, since, at least, Plato. Every philosopher, more or less is preoccupied with it, as an archetypical necessity of both human culture and of philosophy in particular. It is always interesting to see how each philosopher or each person thinks on it, as their thoughts on Death are a departure point and an indication of their whole philosophical system or, for non-philosophers, of their whole way of life. Secondly, it is important to examine this theme in Baudrillard because it inseparably interconnects, explains, and is explained by all the other, key, and the less prominent themes in his philosophy (if it is possible to divide themes in the corpus of a philosopher in such a way). Baudrillard’s thinking might take new dimensions when viewed through his thoughts on Death. Finally, Baudrillard is considered a difficult thinker, because, unlike other philosophers, he grasps themes which people are used to seeing as the pre-occupation or within the realm of fiction, even science-fiction (robots, clones, hyper-reality – The Matrix film). I would like to show, using simple language, that his philosophy, especially surrounding the subject of Death, is completely naked of any metaphysical, romanticised, fantastic, or fiction-like properties; it is realistic and political.
Keywords: Death; Philosophy